2008
DOI: 10.1016/j.jss.2007.12.788
|View full text |Cite
|
Sign up to set email alerts
|

Mold-Shaped, Nanofiber Scaffold-Based Cartilage Engineering Using Human Mesenchymal Stem Cells and Bioreactor

Abstract: Background-Mesenchymal stem cell (MSC)-based tissue engineering is a promising future alternative to autologous cartilage grafting. This study evaluates the potential of using MSCs, seeded into electrospun, biodegradable polymeric nanofibrous scaffolds, to engineer cartilage with defined dimensions and shape, similar to grafts used for subcutaneous implantation in plastic and reconstructive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 34 publications
(30 reference statements)
0
35
1
1
Order By: Relevance
“…124 Others have investigated multicomponent scaffolds, where a gelatinous core is established (by injection) in the mid-substance of a nanofibrous sheet for intervertebral disc applications. 125 Still others have begun to investigate how layers of nanofibers can be seeded with cells, and then stacked to achieve anatomic forms such as periodontal ligament 126 as well as more complicated structures recreating the anatomic form of the IVD and the knee meniscus 127,128 (Fig.…”
Section: Reconstituting Anatomic Formmentioning
confidence: 99%
“…124 Others have investigated multicomponent scaffolds, where a gelatinous core is established (by injection) in the mid-substance of a nanofibrous sheet for intervertebral disc applications. 125 Still others have begun to investigate how layers of nanofibers can be seeded with cells, and then stacked to achieve anatomic forms such as periodontal ligament 126 as well as more complicated structures recreating the anatomic form of the IVD and the knee meniscus 127,128 (Fig.…”
Section: Reconstituting Anatomic Formmentioning
confidence: 99%
“…Therefore, this adhesive property of the nanofibrous scaffold should also be considered as beneficial to stabilization of the meniscal circumferential fibers, thus contributing to the functional preservation of the hoop structure and perhaps preventing the development of osteoarthritis. Morphologically, the aligned nanofibrous scaffold has the structural anisotropy of fiber arrangement similar to that of meniscal collagen fibers, 18,19 and may work as ''a bridge'' to prevent widening of the gap at the torn site until the lesion is completely healed. In addition, the scaffold allowed successful cell infiltration and the deposition of a fibrocartilaginous matrix containing collagen and proteoglycan.…”
Section: Discussionmentioning
confidence: 99%
“…17 In our previous studies, we have observed that adult mesenchymal stem cells (MSCs) cultured on aligned poly(ecaprolactone) (PCL) nanofiber scaffolds fabricated by electrospinning organize and deposit collagen along the fiber direction, producing cartilage-like engineered constructs. 18,19 On the other hand, one drawback of electrospun materials is that the structure is quite dense, which can limit cell infiltration into the scaffold. 20 Also, this feature may influence the adhesive property to native tissue.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study did not discuss the related indexes of the scaffold. In subsequent studies, we will assess new scaffold materials, electrostatic spinning (Agarwal et al, 2008;Janjanin et al, 2008;Wright et al, 2010), and cell-chip technology (Kaneshiro et al, 2006;Mitani et al, 2009;Tani et al, 2010;Weder et al, 2010), and in more detail compare the properties of the engineered cartilages with normal cartilages.…”
Section: Discussionmentioning
confidence: 99%